Enhancing Customer Trust and Value for E-Commerce Sustainability - Sherly Aprillia; Elistia Elistia (Universitas Hayam Wuruk Perbanas, 2023)
The rapid growth of online shopping in e-commerce applications emphasizes the role of after-delivery services provided by online sellers in gaining trust, satisfaction, and repurchase intention. Good after-delivery service and positive customer perceived value contribute to creating customer trust, which also affects repurchase intention. This paper aims to analyze the effect of after-delivery service, customer perceived value, and customer satisfaction on trust to increase repurchase intention. This research was conducted in Jakarta with a causality descriptive research design using a quantitative approach and purposive sampling technique. Data was collected from 291 respondents who have used e-commerce applications. The conceptual model underwent an analysis utilizing SEM (Structural Equation Modeling). Research results reveal that after-delivery service impacts customer trust and customer satisfaction positively. Customer perceived value impacts customer trust and satisfaction positively, and customer satisfaction positively impacts customer trust. Customer trust and customer satisfaction positively impact repurchase intention. After service delivery, customer perceived value positively impacts repurchase intention, which is mediated by customer satisfaction. Furthermore, after delivery service, customer satisfaction and perceived value positively impact repurchase intention mediated by customer trust.